2015
DOI: 10.1371/journal.pone.0137629
|View full text |Cite|
|
Sign up to set email alerts
|

Striving for Excellence Sometimes Hinders High Achievers: Performance-Approach Goals Deplete Arithmetical Performance in Students with High Working Memory Capacity

Abstract: We tested whether the goal to attain normative superiority over other students, referred to as performance-approach goals, is particularly distractive for high-Working Memory Capacity (WMC) students—that is, those who are used to being high achievers. Indeed, WMC is positively related to high-order cognitive performance and academic success, a record of success that confers benefits on high-WMC as compared to low-WMC students. We tested whether such benefits may turn out to be a burden under performance-approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Students reported being reticent to make mistakes, indicating high engagement with the creation and learning experience, but also suggesting a high level of anxiety around making mistakes. We did not explore the etiology of this anxiety about making errors; however, others have reported a similar phenomenon in high‐performing students, suggesting that a desire to outperform other students may actually hamper performance (Crouzevialle et al, ). While passive observation of 3D models can help students learn the spatial organization of an anatomical concept, the act of coloring in the resource made this an active learning process stimulating knowledge recall, spatial awareness, and kinesthetic learning (Jensen and Krogh, ).…”
Section: Discussionmentioning
confidence: 92%
“…Students reported being reticent to make mistakes, indicating high engagement with the creation and learning experience, but also suggesting a high level of anxiety around making mistakes. We did not explore the etiology of this anxiety about making errors; however, others have reported a similar phenomenon in high‐performing students, suggesting that a desire to outperform other students may actually hamper performance (Crouzevialle et al, ). While passive observation of 3D models can help students learn the spatial organization of an anatomical concept, the act of coloring in the resource made this an active learning process stimulating knowledge recall, spatial awareness, and kinesthetic learning (Jensen and Krogh, ).…”
Section: Discussionmentioning
confidence: 92%
“…This suggests that performance pressure hinders individuals who are the most qualified to succeed because it consumes a significant part of their executive resources. Crouzevialle, Smeding, and Butera (2015) showed that the disruption of performance in individuals with high WMC depends on how threatening evaluation is (e.g., because of status-related concerns).…”
Section: Reduced Cognitive Control In the Presence Of Conspecificsmentioning
confidence: 99%
“…In follow-up research, the same authors tested whether this performance-approach goal-related interference could be even amplified for high-working memory capacity students, that is, those students who are used to be high achievers. The pursuit of performance-approach goals should indeed represent a high-stakes opportunity to reaffirm their positive status (Crouzevialle, Smeding, & Butera, 2015). The authors manipulated the presence versus absence of a bogus ranking feedback – either average or very high – in order to generate uncertainty versus confidence regarding the chance to subsequently get a high score and outperform others, in other words the expectation of success given their goals (cf., Wigfield & Eccles, 2000).…”
Section: The Effects Of Performance-approach Goals On Working Memorymentioning
confidence: 99%